Praktik Kepemimpinan Kepala Sekolah dalam Menyupervisi Pendidikan Agama Islam di Sekolah Menengah Pertama - Dewi Nasru' Izatin; Suko Susilo (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2022)
The study was on the back of an accelerating at the SMP Al-Ikhlas Tarokan, with the headteacher's leadership who carried out the supervision of Islamic Religious Education. In this case, researchers observe the headmaster's supervised Islamic Religious Education supervision. The problem with this research includes 1) how does the principal practice leadership in carrying out Islamic Religious Education supervision at the SMP Al-Ikhlas Tarokan? 2) how does the principal's leadership practice implication in supervising Islamic Religious Education at the SMP Al-Ikhlas Tarokan? The research method of this study is a qualitative approach. This study's results were: 1) the headteacher's leadership practice of producing Islamic Religious Education supervisions on the Islamic Religious Education at the SMP Al-Ikhlas Tarokan effective. The principal affects his subordinates with a power referent power that uses leadership with a charismatic leadership style. 2) the implication of the principal leadership practice in performing Islamic Religious Education supervision at the SMP Al-Ikhlas Tarokan is quite good.